Employee Perspectives on Decent Work and Job Burnout: Evidence from Nepalese Manufacturing Industries - Shrestha, Prakash (The International Research Journal of Management Science, 2022)
Purpose: This study aims to explore the relationship between decent work and job burnout. Design/methodology/approach: The study employs a structured questionnaire for the survey. It takes into account three factors of job burnout and seven dimensions of decent work to determine whether there is any association between them. The sample includes 600 people from four industrial estates (including 40 manufacturing industries and 15 employees in each) in Nepal. Findings: The findings supported the idea that there is a strong negative link between decent work and job burnout. Adequate working time and workload, meaningful remuneration, and fundamental principles and values at work are the components of decent work that predict a negative association with job burnout best. It seems that employees are more prone to experience burnout when these characteristics, which can be inserted in the many parameters of decent work, are lacking. Employees can combine work and personal duties and progress professionally with decent work and its dimensions. Research limitations/implications: Only a few manufacturing industries among Nepal's four industrial estates are the focus of this research. The findings of this study hence might not apply to all business groups. Practical implications: Decent work dimensions assist in lowering workplace stress among employees. Reduced job burnout improves both work and quality of work life. Originality/value: This research establishes the relationship between decent work and job burnout, to the author's knowledge the first of its kind in the context of Nepalese manufacturing industries.